Analisis Faktor-Faktor yang Mempengaruhi Pengelolaan Keuangan pada Generasi Muda Profesional: Peran Fintech, Literasi, dan Perencanaan Finansial - Indriani, Lau Rensia Riri; Girsang, Marianus Jhon Libert; Silalahi, Donalson; Sitompul, Pandapotan (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the influence of financial technology (fintech), financial literacy, and financial planning on financial management among young professionals using a descriptive quantitative approach and Structural Equation Modeling - Partial Least Squares (SEM-PLS) method. Data were collected through questionnaires distributed to 200 respondents aged 22–35 who are professionally employed in various sectors. Data analysis was conducted using SmartPLS software. The results show that all three independent variables—fintech, financial literacy, and financial planning—have a positive and significant effect on financial management. Financial literacy was found to be the most dominant influencing factor. These findings emphasize that enhancing financial knowledge, planning capabilities, and the wise use of financial technology plays a crucial role in shaping sound financial behavior among young professionals